Statistical Power Function of Average Control Charts for Non-Normal Data - Singh, J.R; Mishra, U (International Journal of Computer Sciences and Engineering, 2025)
A mathematical investigation has been made to examine in what way the power function of the usual control chart for mean based on the assumption of normality is affected when the characteristics of an item possesses a non-normal distribution specified by the first four terms of an Edgeworth series. Power functions for known standard deviation have been considered and expressions giving corrections due to parental skewness and kurtosis have been obtained in addition to the normal theory expression